Espírito de Seleção : um estudo dos discursos midiáticos a partir da Copa do Mundo de 2006 - Freitas, Gustavo da Silva (2009)
The failures of the Brazilian team football in World Cup of 2006 revive the discussion of representativeness which a selection may or may not take on cultural characteristics and football which represents the nation. The collective feeling of defeat before the performance is not expected in the German camps composed implosion of a scenario of an identity for the Brazilian Team Football. This deconstruction of a model that was unsatisfactory is beyond its scope of decommissioning in quarter-final against the French selection generating, on a renovation highlighted by the change in technical command, the search for new players for the construction of other identities. Assuming that this identity is the result of a discursive process never completed (HALL, 2000; LACLAU, 1996) but which responds to a historical emergency, this study aims to examine how to set that process mapping and analyzing the agency's were and are being put into practice and how the press is involved and participating in the reconstruction of a new image, a new collective feeling, finally, other identities for the Brazilian team. The choice of media field (BOURDIEU, 2002; CHARAUDEAU 2006) as reference the empirical relevance of this before the actual sporting events with respect to the production of multiple meanings that they establish a dialogue between practice and discursive formation of identities. A dialogue that is the result of a constant state of war between the ways that identity is seen by the channels of communication. For the study was used, primarily, the methods of analysis of discourse from the perspective suggested by Michel Foucault (1998) which, combined with cartographic elements (ROLNIK 2006), allowed the meeting of different discourses that within a regularity, proliferated on these events. When selecting texts for the analysis that we can see that it is much more than a homogenization or a meta discourse, the field of media effects truth from a multitude a discourse that seeks to define reality. This range also meets a demand discursive unfinished, something that is constantly reconfiguring from listed and produced by the embedded media field, causing changes, reaffirmations , and early disappearance of certain components of the identities.